Tinjauan Literatur Sistematis tentang Penerapan Pemrograman Linear untuk Optimalisasi dalam Konteks Pendidikan - Muflihah Muham; Prima Cristi Crismono (Media Pendidikan Matematika, 2025)
This study aims to conduct a systematic review of the application of Linear Programming (LP) in optimizing educational management. The method employed is a Systematic Literature Review (SLR), with the literature selection process following the PRISMA framework by reviewing articles from the Scopus database published between 2015 and 2025. The analysis reveals that LP plays a significant role in addressing educational challenges such as class scheduling, resource allocation, and budget management. Moreover, the application of LP also contributes to the development of students’ analytical skills through practical mathematical modeling. The findings indicate that LP not only offers optimization solutions in educational management but also enhances students’ analytical abilities through data-driven decision-making and mathematical modeling. However, the study also identifies several critical gaps, including the lack of LP integration into basic curricula, limitations of models in accounting for social and emotional variables, and challenges in dealing with uncertain data. The study recommends the development of more contextual and integrative LP-based learning models using a multi-criteria approach. The novelty of this research lies in the formulation of a conceptual framework that combines LP with real-world, project-based interdisciplinary learning as a foundation for developing data-driven educational innovations.